Electronics computer aided design - Syafeeza Ahmad Radzi (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
The book provides detailed description and explaination of the important concepts and techniques in electric circuit design. It covers three common electronic computer aided tools for desinging and drafting which are Multisim, PSpice and MATLAB, each in a different chapter.